Studi Keselarasan dan Keterkaitan Bentuk Arsitektur Islam pada Masjid di Kota Kendari - Al Muhran Medi; Hudi Sontha; La Pande Jurumai (Jurnal Inovasi Sains dan Teknologi (INSTEK), 2022)
Islamic architecture is a way to connect the relationship between humans, the environment and the Creator. One symbol of the use of Islamic architecture is the mosque. The purpose of this study is to see the harmony of Islamic architecture in several mosques in Kendari City. The research method used is descriptive and qualitative methods, starting with problem formulation, and data collection through literature surveys and field observations on Islamic architecture in mosques. In the observation and documentation stage, it was found that several mosques in Kendari City have implemented Islamic architecture which can be seen from the characteristics of the mosque, the application of Islamic principles to its architecture and the transformations of mosque forms. From the results of the data found that there are ten mosques in the city of Kendari that have implemented Islamic architecture, namely Al-Alam Mosque, Al-Kautsar Mosque, Arraudah Mosque, Jami'al Falah Mosque, Baitul Rahman Kendari Mosque, Haji Latjinta Hidayatullah Mosque, Abul Ashim Mosque , H.M Jusuf Abadi Mosque, Nurul Fauzan Mosque, Al-Amanah Mosque. From several mosques that have been studied, it shows that the use of Islamic architecture is very much and has a good influence among the people in Kendari City.